TERLAHIR DALAM KARYA SENI LUKIS - ARDIANSYAH, Drs. Achyar Sikumbang, Drs. Erfahmi, M.sn (Serupa The Journal of Art Education, 2014)
This thesis aims to visualize phenomena that occur in children and assess the reality of children's lives in the community and its influence on the environment so noteworthy development. Furthermore, in this thesis, prefers small children as its main object is then packaged in a monochrome paintings, so that what the author wanted to convey can be easily understood. At the end of the 10 works to display a variety of problems that occur in children. The source of this idea is derived from the combination of several news and articles are collected by using the methods and conclusions refer to various children's behavior. Visualize the image in the form of paintings that tell the change in attitude of the children outside its capacity.Kata kunci : Terlahir, Seni Lukis